(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
While studies on African Englishes have proliferated, research on the development of the Zimbabwean variety remains limited. This qualitative study explores the emergent linguistic characteristics of Zimbabwean English in WhatsApp-mediated communication among high school students in Harare. Through a Content Analysis of 4500 WhatsApp messages and Focus Group Discussions with 90 purposively sampled participants, the study reveals a dominant use of new English words, with neologisms being the most prevalent form. The findings also show users’overwhelmingly positive attitude toward the new language and the multifaceted communicative role of these linguistic innovations, although confined to informal communication. Guided by Schneider’s Dynamic Model, the study argues that these results reflect the Nativization phase of ZE, characterized by the emergence of local linguistic features, a shift towards Endonormative stabilization, and the development of a distinct, localized variety of English. The study also offers insights into the complex dynamics of language change in digital social networking sites. It concludes that digital communication is shaping the development of postcolonial English varieties, highlighting the need to reevaluate traditional language standardization. Recommended is that language educators and policymakers should recognize the importance of digital communication in language development and support creative language use in informal digital contexts.